2021
DOI: 10.1002/jsfa.11558
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of contact insecticides and high temperatures on Mediterranean flour moth,Ephestia kuehniellaZeller (Lepidoptera: Pyralidae)

Abstract: BACKGROUND Mediterranean flour moth or mill moth Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) is a common pest of cereals and flour throughout the world. In this study, eggs, third instar larvae, pupae and adults of E. kuehniella were exposed to five elevated temperatures at a range of 45 to 65 °C for 5, 8, 10, 14, 18, 23 and 30 min. The effect of cypermethrin and dichlorvos was assessed on third instar larvae. The larvae were exposed to the insecticides on glass and concrete arenas and their mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Not surprisingly, we found that exposure to 30 • C did not result in a considerable mortality of the different E. kuehniella life stages, which can be considered expectable given that this temperature is suitable for the development of this species [11,32]. However, the "jump" from 30 to 40 • C resulted in a high mortality, which was close to 100% for eggs and larvae, and 100% for pupae and adults, provided that the exposure is 24 h. Given that the usual target temperature and exposure level for commercial heat treatments is 50 • C [13,22,23], our data show that E. kuehniella is likely to be more susceptible to heat than the other stored product insects, which can be considered in commercial heat treatments.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Not surprisingly, we found that exposure to 30 • C did not result in a considerable mortality of the different E. kuehniella life stages, which can be considered expectable given that this temperature is suitable for the development of this species [11,32]. However, the "jump" from 30 to 40 • C resulted in a high mortality, which was close to 100% for eggs and larvae, and 100% for pupae and adults, provided that the exposure is 24 h. Given that the usual target temperature and exposure level for commercial heat treatments is 50 • C [13,22,23], our data show that E. kuehniella is likely to be more susceptible to heat than the other stored product insects, which can be considered in commercial heat treatments.…”
Section: Discussionmentioning
confidence: 57%
“…The available data for heat under laboratory conditions for E. kuehniella are relatively few and definitely less than those for cold. Sadeghi et al [10] tested the effect of microwave heating on larvae of E. kuehniella and found complete mortality at 900 W for 50 s. In a recent study, Javanshir et al [11] tested different life stages of E. kuehniella at elevated temperatures in combination with two different insecticides (cypermethrin and dichlorvos) and found that susceptibility to high temperatures can be influenced by life stage. In that study, the authors reported that pupa may be the most heat-tolerant life stage [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation